2022
DOI: 10.1177/23969415221099397
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the academic achievement of primary and secondary school-aged students with developmental language disorder

Abstract: Background and aims The ability to communicate is a fundamental skill required to participate in school. Students with Developmental Language Disorder (DLD) have persistent and significant language difficulties that impact daily functioning. However, the impact of DLD on the academic achievement of primary and secondary school-aged students has received limited attention. Methods A systematic review of the empirical research published between 2008 and 2020 was undertaken to identify studies that have examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 83 publications
0
17
0
Order By: Relevance
“…social difficulties) that contribute to anxiety symptoms. Furthermore, comorbidly impaired language and working memory are also likely to affect and even limit social and academic functioning, which in turn would be expected to increase anxiety, particularly in the school context ( Young et al, 2002 ; Gathercole et al, 2004 ; Astle et al, 2019 ; Finning et al, 2019 ; Ziegenfusz et al, 2022 ); indeed, it is known that AHDN children are at greater risk of poor school outcomes ( Bethell et al, 2012 ). However, our results also suggest that anxiety is not a parent-perceived experience for all AHDN children, given 53% of our AHDN sample display low/normal levels of anxiety, and similarly there were some AHDN children who had stronger and more neurotypical working memory and language performances.…”
Section: Discussionmentioning
confidence: 99%
“…social difficulties) that contribute to anxiety symptoms. Furthermore, comorbidly impaired language and working memory are also likely to affect and even limit social and academic functioning, which in turn would be expected to increase anxiety, particularly in the school context ( Young et al, 2002 ; Gathercole et al, 2004 ; Astle et al, 2019 ; Finning et al, 2019 ; Ziegenfusz et al, 2022 ); indeed, it is known that AHDN children are at greater risk of poor school outcomes ( Bethell et al, 2012 ). However, our results also suggest that anxiety is not a parent-perceived experience for all AHDN children, given 53% of our AHDN sample display low/normal levels of anxiety, and similarly there were some AHDN children who had stronger and more neurotypical working memory and language performances.…”
Section: Discussionmentioning
confidence: 99%
“…Although the latter method incorporates review elements, it focuses on producing a comparable quantified analysis across studies. The systematic review reported here shared 16 studies with Joye et al (2019), 16 studies with Graham et al (2020), and eight studies with Ziegenfusz et al (2022).…”
Section: Rationale For a Systematic Reviewmentioning
confidence: 99%
“…However, two meta-analyses have been conducted, one each for spelling (Joye et al, 2019) and writing (Graham et al, 2020). Furthermore, a systematic review has been performed that included literacy skills as part of a wider review of academic achievement (Ziegenfusz et al, 2022). Joye et al ( k = 32) found, across the studies they analyzed, that children with DLD produced spelling outputs that were poorer than those produced by age-matched peers.…”
Section: Rationale For a Systematic Reviewmentioning
confidence: 99%
“…For example, children with speech sound disorders show lower academic skills compared to their peers without speech sound disorders, and severity is negatively correlated with reading and spelling abilities ( Bird et al, 1995 ; Webster et al, 1997 ; Lewis et al, 2000 ). Similarly, children with developmental language delay show lower literacy (reading and writing) skills compared to children without developmental language delay ( Ziegenfusz et al, 2022 ). The emphasis on verbal communication skills in the U.S. educational system spotlights the deficits among children with SLDs.…”
Section: Introductionmentioning
confidence: 99%